Determinação das propriedades ópticas e térmicas dos monocristais TGS:Cr3+, SBN:Nd3+ e YVO4:Nd3+ em função da temperatura - Nunes, Alcir Rosa (2007)
In this work the thermal lens spectrometry, the thermal relaxation calorimetry and the optical interferometry were applied to measure the thermo-optical properties of TGS:Cr3+, SBN:Nd3+ and YVO4:Nd3+ single crystals. The thermal lens measurements were carried out with polarized lasers (excitation and probe beams), and the interferometric experiments were carried out with a polarized laser beam. The crystal axes were aligned parallel to the electrical field of the laser beams and the measurements were performed in each axis independently. In the thermal lens measurements the thermal diffusivity and the parameter θ, which describes the thermal lens signal amplitude, were obtained. The thermal relaxation calorimetry method was employed to determine the specific heat, and the optical interferometry to determine the temperature coefficient of the optical path length. The measurements carried out in the TGS:Cr3+ showed strong changes in the θ parameter values in the ferroelectric to paraelectric phase transition, around 46°C. This also occurred with thermal diffusivity data, except for the orientation in which the electrical field was parallel along the B axis. The phase transition for the SBN:Nd3+ single crystal occurred around 62°C. In this sample we observed the occurrence of photorefractive effects which demanded the use of appropriate excitation beam spot sizes to obtain the thermal lens effect. The thermal diffusivity and specific heat data for the YVO4:Nd3+ single crystal were used to determine the temperature dependence of the thermal conductivities as a function of the sample orientation. For the three studied samples, the thermal lens data provided the thermal diffusivity and the parameter θ related to the beam electrical field polarization, what suggests the need of a new anisotropic theoretical model for the thermal lens effect taking into account the anisotropy of the thermal parameters present in the thermal diffusion equation. In conclusion, the results of this work provided important information about the temperature dependence and the anisotropy of the thermo-optical properties of three single crystals, TGS:Cr3+, SBN:Nd3+ and YVO4:Nd3+. For TGS:Cr3+ and SBN:Nd3+ the measurements were performed along the ferroelectric to paraelectric phase transition temperatures. The results suggest that the adopted procedure of this work may be useful in the study of single crystals used as opto-electronic devices.